2018
DOI: 10.1590/1678-457x.15817
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of season, sex and size on nutrient composition of freshwater crayfish (Astacus leptodactylus Eschscholtz, 1823) from Lake Eğirdir

Abstract: Astacus leptodactylus is naturally and widely distributed in lakes, ponds and rivers throughout Turkey (Harlioğlu & Harlioğlu, 2004). On recent years, there has been a gradual decrease in the production of crayfish in Turkey from 5000 tons in 1984 to 532 tons in 2015 (Turkish Statistical Onstitute, 2017). The greatest cause of this decline is crayfish plague fungus (Aphanomyces astaci) seen after 1985 (Baran et al., 1987; Rahe & Soylu, 1989; Harlioğlu, 2008). There is no crayfish culture in Turkey and all prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Overall, males had higher lipid content than females, except in September. Some studies have reported the opposite for crayfish, where females were found to have higher total lipid content (Bahadır Koca and Argun Uzunmehmetoğlu 2018 ). However, Mona et al ( 2000 ) found higher fat levels in male individuals and attributed this to the demand for these materials during the active metabolic processes required for the rapid completion of their life cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, males had higher lipid content than females, except in September. Some studies have reported the opposite for crayfish, where females were found to have higher total lipid content (Bahadır Koca and Argun Uzunmehmetoğlu 2018 ). However, Mona et al ( 2000 ) found higher fat levels in male individuals and attributed this to the demand for these materials during the active metabolic processes required for the rapid completion of their life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of crustacean biochemistry, it has been observed that factors such as sex, reproductive period (Buckup et al 2008 ), environmental parameters like habitat, feeding activity, and food availability (Buckup et al 2008 ), as well as seasonality (Bahadır Koca and Argun Uzunmehmetoğlu 2018 ), can influence their metabolism and biochemical composition. Lipids, as the main organic reserve in many crustaceans, play a significant role in the metabolic processes of these species.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is susceptible to spoilage just like fish and other seafood and should be consumed fresh immediately after harvest, or measures should be taken to preserve its original freshness as much as possible. Therefore, adequate packaging technologies need to be developed for the preservation of fish or other foods (Bahadır Koca & Argun Uzunmehmetoğlu, 2018;Ojagh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%